Nutritional status, growth, dietary intake in asthmatic children: a study to Junior High Schools in Yogyakarta municipality. - Elisa Elisa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Objective: To know the relationship between asthma and nutritional status, growth, and dietary intake. Design: Prospective cohort study of children aged 12-18 years.Setting: Twenty eight Junior High Schools in Yogyakarta municipality.Subjects: There were 802 children who ever had symptoms of asthma and children who never had asthma as control. Questionnaire was used to establish the diagnosis of asthma. Subjects were grouped as: 1) ever had symptom of asthma but not in the last 6 months; 2) ever had 1 symptom of asthma in the last 6 months; 3) ever had 2 symptoms of asthma in the last 6 months; 4) ever had 3 symptoms of asthma in the last 6 months; and 5) never had asthma.Main outcome measures: Z-score for weight for age and height for age, body mass index (BMI), and dietary intake.Results: This study revealed there was no statistical difference between asthmatic group and control group in nutritional status based on weight for age in the first measurement (p=0.292), the second (p=0.258), and the third (p=0.122); based on height for age, in the first measurement (p=0.356), the second (p=0.541), the third (p=0.384). Likewise, based on body mass index, in the first measurement (p=0.335), the second (p=0.305), the third (p=0.166). Concerning growth there was no statistical difference between asthmatic group and control group based on weight for age from the first to the second measurement (p=0.215), second to third Ip=0.866), first to third (p =0.188); based on height for age from the first to the second measurement Ip=0.774), second to third (3=0.627), first to third (p=0.738ï€´. Likewise, based on body mass index from the first to the second measurement (p=0.556), second to third (p=0.913), first to third (p=0.784). Daily intake of nutrition revealed there was no statistical difference between asthmatic group and control group concerning calorie (p=0.075), protein (p=0.345), fat (p=0.989), carbohydrate (p=0.731), calsium (p=0.936), iron (p=0.566), vitamin A (p=0.457), vitamin B (p=0.932ï€´, and vitamin C (p=0.837).Conclusion: Asthma did not affect nutritional status, growth, and dietary intake. There was no significant difference on growth among study groups.Key words: asthma - nutritional status - growth - dietary intake